Hebella Allman 1888 - Schejter, L.; Genzano, G.; Pérez, C. D.; Acuña, F.; Cordeiro, R. T. S.; Silva, R. A.; Garese, A.; Bremec, C. S. (Zenodo, 2020)
Hebella sp. Material examined: BBB 2016: St. 5; St. 27; St. 32; St. 38; St. 39. Remarks: Scarce colonies attached on other hydroids ( Abietinella operculata and S. subdichotomus ) and on tubes of the polychaetes Chaetopterus antarcticus were found. Alike the genus Filellum , identification of Hebella to specific level is not possible when the material lacks reproductive structures. However the nominal species Hebella striata Allman, 1888 was widely reported in Argentinean continental shelf. Published as part of Schejter, L., Genzano, G., Pérez, C. D., Acuña, F., Cordeiro, R. T. S., Silva, R. A., Garese, A. & Bremec, C. S., 2020, Checklist of Benthic Cnidaria in the SW Atlantic Ocean (54 ºS- 56 ºS), pp. 201-239 in Zootaxa 4878 (2) on page 210, DOI:10.11646/zootaxa.4878.2.1, http://zenodo.org/record/4424884